Analysis of macrophage interactions with cryopreserved amastigotes of Leishmania tropica. - Hoover, D L (1983)
Amastigotes of Leishmania tropica were harvested from infected footpads of BALB/cJ mice and cryopreserved, using a controlled-rate freezer. This technique produced inocula with reproducible viability and infectivity for peritoneal macrophages from C3H/HeN mice. Cryopreserved amastigotes, stored for up to 17 weeks in a liquid nitrogen freezer, were similar to freshly harvested parasites in susceptibility to lymphokine-induced intracellular killing. Interactions of cryopreserved parasites with macrophages were best evaluated at 72 h, since macrophages preferentially ingested viable amastigotes and rapidly cleared ingested nonviable parasites.